1997
DOI: 10.1007/s004670050311
|View full text |Cite
|
Sign up to set email alerts
|

Increased recognition of IgA nephropathy in African-American children

Abstract: Based upon the percentage of cases of IgA nephropathy (IgAN) in biopsy series, a lower prevalence has been assumed for African-Americans compared with Americans of European descent. This may be due to a racial difference in the basic underlying pathology of IgAN or to racial differences in patterns of referral and biopsy selection practices. Over the past decade (1985-1994), we have found similar incidences of IgAN in Caucasian and African-American children from Shelby County, Tennessee. The incidence was 3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…These differences reflect whether urine-screening programs are performed and the different approaches adopted in obtaining renal biopsy specimens in the various geographic areas [7, 21, 24, 25]. Moreover, Jennette et al [26]reported that the incidence of IgA nephropathy was approximately sixfold lower in blacks in 1985; however, Wyatt et al [19]and Sehic et al [27]reported recently that the incidence of IgA nephropathy was equal or more common in blacks. The prevalence of urinary abnormalities was similar in various geographic areas and races [3, 4], including the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These differences reflect whether urine-screening programs are performed and the different approaches adopted in obtaining renal biopsy specimens in the various geographic areas [7, 21, 24, 25]. Moreover, Jennette et al [26]reported that the incidence of IgA nephropathy was approximately sixfold lower in blacks in 1985; however, Wyatt et al [19]and Sehic et al [27]reported recently that the incidence of IgA nephropathy was equal or more common in blacks. The prevalence of urinary abnormalities was similar in various geographic areas and races [3, 4], including the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Because our department provides all third round school urinalysis screening and performs all pediatric renal biopsies in Nishinomiya City, Hyogo Prefecture, we are aware of nearly all cases of pediatric IgA nephropathy diagnosed in Nishinomiya City. Table 6 provides literature citations for the number of cases of pediatric IgA nephropathy per 100,000 children in the pediatric population [4][5][6][7]. The age range of the patients in each study exhibits some variation, rendering comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Although some centers have reported that IgAN was rare in AA cohorts (4 -7), others have shown incidence rates in Caucasians and AA populations to be similar (8,21). Data from the African American Study of Kidney Disease also suggest that IgAN may be rare in African Americans (22).…”
Section: Discussionmentioning
confidence: 99%